SYNTHESIS, CHARACTERIZATION AND BIOLOGICAL EVALUATION OF NOVEL CHALCONE DERIVATIVES OF IMIDAZOLONES - ANITHA SADULA; SUBHASHINI N J P (International Journal of Pharma and Bio Sciences, 2014)
A series of six 4-arylidene-2-phenyl-1-(4-(3-phenylacryloyl)phenyl)-1H-imidazol-5(4H)ones (8a-f) have been synthesized by condensation of 1-(4-acetylphenyl)-4-arylidene-2phenyl-1H-imidazol-5(4H)-ones (7a-e) with different aryl aldehydes (4a, 4c, 4f). The structures of the newly synthesized compounds were characterized by FT-IR, 1H NMR, 13C NMR and Mass spectral studies. All the final compounds synthesized were screened for their antimicrobial and antioxidant activities. 8a, 8d showed potent antibacterial activity whereas all the titled compounds showed highest antifungal activity and 8b showed excellent antioxidant activity.